Telegrama de Frank H. Hitchcock a Roberto H. Todd - Todd, Roberto H.; Hitchcock, Frank H. (My University, 1909)
Telegrama relacionado a felicitaciones de año nuevo.
Keywords: Hitchcock, Frank H.--Correspondence.; Hitchcock, Frank H.--Correspondencia.; Todd, Roberto H.--Correspondencia.; Todd, Roberto H.--Correspondence.